Penggunaan Media Wordwall Dalam Pembelajaran Teks Prosedur Kelas VII-4 SMP Negeri 3 Bayung Lencir - Mastura, Anggun Yuliana; D, Yusra; Harahap, Eddy Pahar (Jurnal Ilmiah Dikdaya, 2024)
This research aims to describe the use of Wordwall in learning procedural texts for class VII-4 of SMP Negeri 3 Bayung Lencir. This research was carried out at SMP Negeri 3 Bayung Lencir, the subject of this research was the Indonesian language teacher Class VII-4 SMP Negeri 3 Bayung Lencir. The approach in this research is a qualitative approach. This type of research is descriptive. The data obtained from this research is in the form of observations of teachers in using Wordwall as a learning medium. The method used in this research is descriptive qualitative. The collection technique in this research uses several methods, consisting of observation, tests and interviews. The aspects assessed in this research are the results of the Indonesian language teacher, namely Mrs. Anggi Susilawati, S.Pd., when implementing learning using Wordwall and the results of the students' work. The results of this research show that the use of Wordwall as a learning medium for class VII-4 narrative text material at SMP Negeri 3 Bayung Lencir is implemented smoothly in accordance with the teaching module. This can be seen from the learning process, starting from the teacher carrying out preliminary activities, then at the core stage the teacher explains, asks questions and determines the results of student work that will be created, the teacher helps students determine the theme, and determines the schedule for collecting student work results, then in the closing activity The teacher concludes the learning that has been carried out.